Expressy: Using a Wrist-worn Inertial Measurement Unit to Add Expressiveness to Touch-based Interactions - Wilkinson, Gerard; Kharrufa, Ahmed; Pursglove, Bradley; Wood, Gavin; Haeuser, Hendrik; Hammerla, Nils; Hodges, Steve; Olivier, Patrick (Proceedings of CHI 2016, 2000)
Expressiveness, which we define as the extent to which rich and complex intent can be conveyed through action, is a vital aspect of many human interactions. For instance, paint on canvas is said to be an expressive medium, because it affords the artist the ability to convey multifaceted emotional intent through intricate manipulations of a brush. To date, touch devices have failed to offer users a level of expressiveness in their interactions that rivals that experienced by the painter and those completing other skilled physical tasks. We investigate how data about hand movement – provided by a motion sensor, similar to those found in many smart watches or fitness trackers – can be used to expand the expressiveness of touch interactions. We begin by introducing a conceptual model that formalizes a design space of possible expressive touch interactions. We then describe and evaluate Expressy, an approach that uses a wrist-worn inertial measurement unit to detect and classify qualities of touch interaction that extend beyond those offered by today’s typical sensing hardware. We conclude by describing a number of sample applications, which demonstrate the enhanced expressive interaction capabilities made possible by Expressy.